The Effect of Empowerment and Quality of Work Life on Teachers’ Productivity - Muhamad Suhardi; Zinnurain Zinnurain (STAI Hubbulwathan Duri, 2022)
This study aims to comprehensively find out the effect of empowerment and quality of work life on teachers’ productivity at Private MTs (Islamic Junior High School) of Praya District, Central Lombok Regency in the Academic Year of 2020/2021. This study used a survey method with path analysis applied in hypothesis testing. This research was conducted on 200 teachers as respondents selected at simple random. Analysis and interpretation of the data shows that (1) empowerment has a direct positive effect on productivity, (2) quality of work life has a direct positive effect on productivity, (3) empowerment has a direct positive effect on quality of work life. It can be concluded that high empowerment results in the increase of the quality of working life of teachers in Private MTs, Praya District, Central Lombok Regency.